Arzneimittelforschung - heute und morgen - Alfred Pletscher (CHIMIA)
Today’s drug research is mainly based on the following three approaches: a) Random screening of newly synthetized compounds in a wide variety of biological test systems. This approach, which is being continued owing to a lack of knowledge on structure- activity relationship, has been getting less and less rewarding, b) Search for active compounds in plant and animal material known or suspected to have biological activity. At present efforts are being focused on Chinese herbs and marine organisms, c) Design of compounds based on a biological hypothesis. By this approach drugs like α-methyldopa, L-dopa and antimetabolites have been developed. Despite considerable successes of modern pharmacotherapy in certain fields, e. g. infectious diseases, some neuropsychiatric disorders, no major breakthrough has been achieved in others, e. g. cancer, arteriosclerosis, rheumatism, schizophrenia, immune diseases. New avenues of research may be opened by recent developments in basic research, e. g. the increasing knowledge on regulatory substances occurring in minute amounts in the mammalian body (e. g. hypothalamic releasing hormones, encephalins), the progress in structure elucidation and synthesis of high molecular weight compounds (e. g. peptides and polynucleotides), the advances in immunology and cell biology as well as in the handling of genetic material. Based on these developments new types of drugs may either be designed by the chemists or obtained by techniques such as culturing of eukaryotic cells or of bacteria transformed by transplantation of mammalian genetic material.